Oral step-down therapy in patients with uncomplicated Staphylococcus aureus primary bacteremia and catheter-related bloodstream infections. (4th July 2022) - Mun, Seok Jun; Kim, Si-Ho; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; Peck, Kyong Ran
Abstract: Patients with uncomplicated Staphylococcus aureus primary bacteremia and catheter-related bloodstream infection (CRBSI) should be treated for at least 14 days. However, evidence for oral step-down therapy is lacking in these patients. A retrospective cohort was identified from 2013 to 2018 in a 1, 950-bed tertiary hospital. An oral antimicrobial therapy (OAT) group was defined as patients treated with oral antibiotics following less than 10 days of intravenous antimicrobial therapy (IAT). Treatment failure was defined as any case of recurrence or death within 90 days. A total of 103 patients were included in the analysis, including 32 patients treated with OAT. Rates of treatment failure were 3.2% and 12.7% in the OAT and IAT groups ( P = 0.113). The length of hospital stay was shorter in the OAT group. OAT was not an independent risk factor for treatment failure. OAT may reduce the duration of hospitalization without adverse effects in these patients.